A novel scaffold geometry for chondral applications: Theoretical model and in vivo validation. Issue 10 (29th July 2014) - Scaglione, Silvia; Ceseracciu, Luca; Aiello, Maurizio; Coluccino, Luca; Ferrazzo, Federica; Giannoni, Paolo; Quarto, Rodolfo
ABSTRACT A theoretical model of the 3D scaffold internal architecture has been implemented with the aim to predict the effects of some geometrical parameters on total porosity, Young modulus, buckling resistance and permeability of the graft. This model has been adopted to produce porous poly‐caprolacton based grafts for chondral tissue engineering applications, best tuning mechanical and functional features of the scaffolds. Material prototypes were produced with an internal geometry with parallel oriented cylindrical pores of 200 μm of radius (r) and an interpore distance/pores radius (d/r) ratio of 1. The scaffolds have been then extensively characterized; progenitor cells were then used to test their capability to support cartilaginous matrix deposition in an ectopic model. Scaffold prototypes fulfill both the chemical‐physical requirements, in terms of Young's modulus and permeability, and the functional needs, such as surface area per volume and total porosity, for an enhanced cellular colonization and matrix deposition. Moreover, the grafts showed interesting chondrogenic potential in vivo, besides offering adequate mechanical performances in vitro, thus becoming a promising candidate for chondral tissues repair. Finally, a very good agreement was found between the prediction of the theoretical model and the experimental data. Many assumption of this theoretical model, hereby applied to cartilage, may be transposed to other tissue engineering applications, such as bone substitutes. Biotechnol. Bioeng. 2014;111: 2107–2119. © 2014 Wiley Periodicals, Inc.